A reciprocal antagonism between miR‐376c and TGF‐β signaling regulates neural differentiation of human pluripotent stem cells. Issue 11 (11th August 2014) - Liu, Juli; Wang, Linli; Su, Zhenghui; Wu, Wei; Cai, Xiujuan; Li, Di; Hou, Jundi; Pei, Duanqing; Pan, Guangjin
Abstract : Differentiation of neural lineages from human pluripotent stem cells (hPSCs) raises the hope of generating functional cells for the treatment of neural diseases. However, current protocols for differentiating hPSCs into neural lineages remain inefficient and largely variable between different hPSC lines. We report that microRNA 376c (miR‐376c) significantly enhanced neural differentiation of hPSCs in a defined condition by suppressing SMAD4, the co‐SMAD for TGF‐β signaling. Downstream, SMAD4 directly bound and suppressed PAX6, the critical neural lineage specification factor. Interestingly, we also found that SMAD4 binds and suppresses miR‐376c clusters in undifferentiated hESCs. In summary, our findings revealed a reciprocal antagonism between miR‐376c and SMAD signaling that regulates cell fate during human neural differentiation.—Liu, J., Wang, L., Su, Z., Wu, W., Cai, X., Li, D., Hou, J., Pei, D., Pan, G. A., reciprocal antagonism between miR‐376c and TGF‐β signaling regulates neural differentiation of hPSCs. FASEB J. 28, 4642–4656 (2014). www.fasebj.org